Wspomnienie o ks. prałacie Romualdzie Biniaku (Kronika Bydgoska, 2010)
Priest prelate R. Biniak was bom in 1941. He came from a deeply religious, patriotic handicraft family. He took holy orders as a priest in 1965, in the period of increased fight against the Church, right before the celebrations of the millennial anniversary of the baptism of Poland. Polish Primate S. Wyszyński appointed him to organise a parish and to supervise the constmction of a church in Wyżyny District, Bydgoszcz. The beginning was difficult. Religion classes were conducted in a poor forester’s lodge, and masses were cele- brated in a provisional chapel. The parish gradually gained morę and morę associations, movements and organisations. A special work of priest Biniak was establishment of a hospice. He also performed his duties as a dean. In recognition of his merits in ministry he became the chairman of the Church Committee of the Visit of Pope John Paul II to Bydgoszcz in 1999. He organised the Days of Christian Culture. He gave shelter to Tadeusz Nowakowski, a writer and editor of “Wolna Europa” (Free Europę). He was the last one to have as a guest at the parish the blessed priest Jerzy Popiełuszko, who was kidnapped and murdered on his way back from Bydgoszcz. He was also a member of the board of the Friends of Bydgoszcz Association. He died on November 27, 2010.